Economic and policy lessons from Japan to developing countries - Toyoda, Toshihisa; Nishikawa, Jun; Sato, Hiroshi San (Palgrave Macmillan, 2012)
Written by fifteen leading academics from the Japan Society for International Development (JASID), this book undertakes a review of Japan's economic development over the last 150 years, and seeks to clarify Japanese priorities in domestic and foreign policy for the coming decades.